Efektivitas Program Pembinaan Prestasi Cabang Olahraga Sepak Bola U-16 PPLP-D Musi Banyuasin - Sunarman Sunarman; Meirizal Usra; Reza Resah Pratama; Hartati; Herri Yusfi; Arizky Ramadhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research aims to specifically discuss the effectiveness of the U-16 PPLP-D Musi Banyuasin soccer achievement training program. This research uses a qualitative approach with the CIPP (Context, Input, Process, Product) model. The data sources in this research were obtained from administrators, coaches and athletes who are members of the U-16 PPLP-D Musi Banyuasin football sport. The research location was carried out at PPLP-D Musi Banyuasin, data collection used interview, observation and documentation methods. The data analysis technique used was data triangulation. The research results show that the Context, background and objectives of the achievement training program are working well. In terms of financial Input, the finances of administrators, coaches and athletes are running well, but there are still deficiencies in terms of infrastructure, especially fitness equipment. The Process, training program and its implementation as well as monitoring have been running well. In terms of Product, the overall achievements of both individuals and teams have been achieved well, as can be seen from the results of the documentation of the achievements achieved by athletes in the U-16 PPLP-D Musi Banyuasin football sport. The research conclusions show that the U-16 PPLP-D Musi Banyuasin football achievement development program is considered effective, but still requires strengthening the aspects of strategic planning and optimizing facilities. It is hoped that the implications of this research will be the basis for improving the management of coaching programs and developing youth sports performance policies at the regional level. Keywords: Development, Football, PPLP-D